2021
DOI: 10.1002/aic.17440
|View full text |Cite
|
Sign up to set email alerts
|

Antibody screening at reduced pH enables preferential selection of potently neutralizing antibodies targeting SARS‐CoV‐2

Abstract: Antiviral monoclonal antibody (mAb) discovery enables the development of antibody‐based antiviral therapeutics. Traditional antiviral mAb discovery relies on affinity between antibody and a viral antigen to discover potent neutralizing antibodies, but these approaches are inefficient because many high affinity mAbs have no neutralizing activity. We sought to determine whether screening for anti‐SARS‐CoV‐2 mAbs at reduced pH could provide more efficient neutralizing antibody discovery. We mined the antibody res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 69 publications
(219 reference statements)
1
5
1
Order By: Relevance
“…These data revealed that the hit selection based on Round 2 ER>5 and VL+ >2 reads was efficient but not perfect. The hit rate was slightly lower compared to our previous studies using human B cell repertoires (72% vs. 90% - 100%), likely due to the larger size of the selected pool for characterization here (~100 vs. ~20 clones), and potentially the differences in B cell tissue origins, cell selection strategies, and sort designs ( 58 , 60 , 61 ). The genuine binding clones from BM and SPL comprised about 5-6% of reads in the BM or SPL clustered populations, further confirming the polarized nature of these antibody libraries ( Tables S4 , S5 ).…”
Section: Resultscontrasting
confidence: 64%
“…These data revealed that the hit selection based on Round 2 ER>5 and VL+ >2 reads was efficient but not perfect. The hit rate was slightly lower compared to our previous studies using human B cell repertoires (72% vs. 90% - 100%), likely due to the larger size of the selected pool for characterization here (~100 vs. ~20 clones), and potentially the differences in B cell tissue origins, cell selection strategies, and sort designs ( 58 , 60 , 61 ). The genuine binding clones from BM and SPL comprised about 5-6% of reads in the BM or SPL clustered populations, further confirming the polarized nature of these antibody libraries ( Tables S4 , S5 ).…”
Section: Resultscontrasting
confidence: 64%
“…B cells were isolated from cryopreserved PBMCs of SARS-CoV-2 convalescent donors as previously described [ 16 , 41 , 54 56 ]. Briefly, B cells were enriched by CD27+ selection and stimulated in vitro for five days to enhance transcription of antibody genes.…”
Section: Methodsmentioning
confidence: 99%
“…Overlap extension RT-PCR was used to transform separate heavy (VH) and light (VL) variable genes into a single, physically linked VH:VL cDNA amplicons. cDNA amplicons encoding heavy and kappa light chain variable regions were cloned into a yeast display vector for expressing antibody VH:VL genes as Fabs for functional screening via FACS and NGS as previously reported [ 16 , 41 , 55 , 56 ]. Briefly, AWY101 yeast expressing Fabs were cultured in SGCAA media (Teknova) with 2 g/L dextrose (SGDCAA) for 36 hrs at 20°C to induce Fab expression for surface display.…”
Section: Methodsmentioning
confidence: 99%
“…B cells were isolated from cryopreserved PBMCs of SARS-CoV-2 convalescent donors as previously described [16, 39, 5052]. Briefly, B cells were enriched by CD27+ selection and stimulated in vitro for five days to enhance transcription of antibody genes.…”
Section: Methodsmentioning
confidence: 99%
“…Overlap extension RT-PCR was used to transform separate heavy (VH) and light (VL) variable genes into a single, physically linked VH:VL cDNA amplicons. cDNA amplicons encoding heavy and kappa light chain variable regions were cloned into a yeast display vector for expressing antibody VH:VL genes as Fabs for functional screening via FACS and NGS as previously reported [16, 39, 51, 52]. Briefly, AWY101 yeast expressing Fabs were cultured in SGCAA media (Teknova) with 2 g/L dextrose (SGDCAA) for 36 hrs at 20°C to induce Fab expression for surface display.…”
Section: Methodsmentioning
confidence: 99%